Prostacyclin (PGI2) inhibits the formation of platelet thrombi in arterioles and venules of the hamster cheek pouch. - Higgs, E A (1978)
1 Isolated rings of hamster aorta produced an unstable substance which inhibited platelet aggregation in vitro and had the same characteristics as prostacyclin. 2 Prostacyclin inhibited adenosine diphosphate (ADP)-induced aggregation of hamster platelets in vitro. 3 The effects of prostacyclin on ADP-induced platelet thrombi in the microcirculation of the hamster cheek pouch were studied with a television microscope. 4 Prostacyclin caused a dose-dependent increase in the time of iontophoretic application of ADP which was required to induce platelet thrombi formation and embolization in venules (30 to 40 micron diameter). 5 Prostacyclin caused a dose-dependent reduction in the total time during which ADP-induced thrombi were observed following local electrical damage to arterioles (40 to 80 micron diameter). 6 Thrombus formation in venules and arterioles was abolished by 500 ng/ml prostacyclin in the Krebs solution superfusing the hamster cheek pouch. 7 Prostacyclin was approximately twenty times more potent than prostaglandin E1 in preventing thrombus formation in the microcirculation.